2020
DOI: 10.37715/jee.v9i2.1453
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of interest factors for entrepreneurship of accounting education students

Abstract: This study aims to determine the various factors that become the interest in entrepreneurship in accounting education students at Universitas PGRI Madiun. This study used a qualitative approach and the type of research was descriptive. The researcher conducted interviews with informants, namely accounting education students at the Universitas PGRI Madiun. The results of this study are that the informants R, Y, T, K and P are interested in entrepreneurship, but the informant (R) has an introverted personality. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Therefore, we should not narrowly interpret it only as a matter of selling but also as planning and evaluation. Leadership attitudes and speaking skills are also needed when entrepreneurship (Pamungkas et al, 2020).…”
Section: Learn To Pioneer With Actdupreneurshipmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we should not narrowly interpret it only as a matter of selling but also as planning and evaluation. Leadership attitudes and speaking skills are also needed when entrepreneurship (Pamungkas et al, 2020).…”
Section: Learn To Pioneer With Actdupreneurshipmentioning
confidence: 99%
“…In line with that, Fahmi et al (2019) state that digital business has a significant impact on supporting entrepreneurship leading to models and formats that are much more flexible and easily accessible to all consumer segments wherever they are. In addition, Pamungkas et al (2020) revealed that essential factors in entrepreneurship are leadership training, public speaking, and entrepreneurial skills.…”
Section: Introductionmentioning
confidence: 99%